Selenium Concentrations in Serum and its Outputs in Milk and Urine from Grazing Jersey Cow Herds Found in Two Dairy Production Regions from Costa Rica - Saborío Montero, Alejandro (2017)
Objective: The study aimed to determine the concentration of selenium (Se) and glutathione peroxidase (GSH-Px) in serum and the Se concentration in milk and urine in grazing Jersey cows in two dairy producing areas of Costa Rica. Methodology: The study was conducted on commercial dairy herds in the highlands of Cartago (≈2250 m of altitude) and Zarcero (≈1750 m of altitude). Cartago cow herds were intensively grazing kikuyu grass (Kikuyuocloa clandestina) and Zarcero cow herds were grazing star grass (Cynodon nlemfuensis). Daily supplementation in both areas consisted of concentrate (16% CP, 1.81 Mcal NEL) according to milk yield (1 kg concentrate: 3 kg of milk). Blood samples were taken from the coccygeal vessels, milk samples were collected individually during milking from the milk yield meter container and urine was obtained using rubbing stimulation technique. From Cartago area, a total of 102, 139 and 87 samples of blood, milk and urine respectively were collected and analyzed. From Zarcero region 66, 84 and 43 samples in the same order were collected and analyzed. Results: Atomic absorption spectrophotometry was used to determine Se concentration. A total of 85 samples from two farms in each region were tested to determine GSH-Px using a glutathione peroxidase activity colorimetric assay kit. The soil was tested in each farm using a soil auger to obtain 20 subsamples per sample, those subsamples were collected drilling the ground surface to a depth of 10 cm and then mixed to generate a composited sample which was analyzed for Se using atomic absorption spectrophotometry. Average serum, milk and urine Se concentration for cows from Cartago and Zarcero were 44.13 (SD = 27.68), 30.94 (SD = 20.13), 78.37 (SD = 60.14) μg Se L–1 and 19.19 (SD = 10.59), 21.82 (SD = 19.07), 14.72 (SD = 6.50) μg Se L–1, respectively. The average GSH-Px concentration in serum was 73.74 and 33.82 for Cartago and Zarcero cows, respectively. Conclusion: High concentrations of selenium in urine in some of the farms and low concentrations of GSH-Px in serum in most of the cows could imply a poor utilization of this mineral, leading to deficiencies to meet metabolic requirements and therefore to associated economic losses.